Formulation and Characterization of Antioxidant Capsules Containing Cantigi Extract-loaded Nanoparticles Synthesized Via Nanoprecipitation Method - Kosasih, Kosasih; Deny Susanti; Immanuel Puji Hosanna Asianski; Dede Irving Maryanto (Journal of Natural Product for Degenerative Diseases, 2024)
Cantigi extract exhibit numerous activities, including antioxidants. Various dosage forms have been developed, except a capsule formulation. Capsule formulation offers numerous advantages. Objectives: To prepare and characterize the cantigi extract, extract-loaded nanoparticles, capsules containing extract, and capsules containing nanoparticles as antioxidants. Methods: The Cantigi extract was prepared using the maceration method and characterized for both specific and non-specific parameters. The preparation of extract-loaded nanoparticles utilized the nanoprecipitation method with gelatin, poloxamer, and glutaraldehyde as the polymer, stabilizer, and crosslinker, respectively. Characterization of the nanoparticle included particle size, polydispersity index, zeta potential, and entrapment efficiency. Capsule formulation (F): F1 contained the extract, while F2 contained the nanoparticles. Capsule characterization involved assessment of content uniformity, weight variation, disintegration, and release profile. Antioxidant activity was measured using the DPPH method for extract, nanoparticles and capsules. Results: The cantigi extract met specific and non-specific parameters. Nanoparticle size was found to be 235.8+12.62 nm with a polydispersity index of 0.226+0.050, a zeta potential of -8.53+0.27 mV, and an entrapment efficiency of 52.69+1.06%. Characteristics of F1 and F2 included content uniformity of 97.24+4.23 and 89.86+1.48%, weight variation of 185.5+1.31 and 127.22+1.86%, disintegration time of 3.67-4.08 and 5.35-5.97 minutes, extract content of 97.24+4.23 and 89.86±1.48%, and release rate of 86.78+3.98 and 61.79+3.48%, respectively. Antioxidant activities of the extract, extract-loaded nanoparticles, and capsules (F1 dan F2) were determined to be 17.40+0.94, 33.60+1.85, 66.81+1.46, and 106.61+3.32 ppm, respectively. Conclusion: Cantigi extract and nanoparticles exhibited potent antioxidant activities while meeting quality parameters. The capsule formulation displayed varying antioxidant activities and release profiles, with capsules containing nanoparticles demonstrating a sustained release profile.